2022
DOI: 10.17081/psico.25.48.5500
|View full text |Cite
|
Sign up to set email alerts
|

Conducta sexual en jóvenes universitarios: Estudio de revisión

Abstract: Objetivo: Describir y analizar estudios sobre la conducta sexual en jóvenes iberoamericanos. Método: Revisión bibliográfica de 150 referencias, tomadas de las bases de datos Web of Science, Latindex, Scopus, ProQuest, Redaly, Scielo, Ebsco. Se hizo análisis de calidad mediante el uso de la Herramienta de Evaluación de Métodos Mixtos (MMAT) para 91 artículos finales. Resultados: Existe bibliografía sobre las conductas sexuales del dominio corporal, poca del dominio social; la edad de inicio de la ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…This can increase risky sexual behaviors such as having multiple sexual partners, engaging in unprotected sexual relations, consuming drugs and alcohol before sex, and using dating apps, among other situations that warrant further study in Medellín. [29][30][31][32][33] The prevalence of HIV was higher in MSM without health insurance affiliation, aligning with a previous study in Colombia that found an infection prevalence of 25% in unaffiliated individuals, 17% for individuals under the subsidized regime, and 9.8% in the contributory regime. Understanding that unaffiliated and subsidized regime individuals correspond to groups without formal employment that involve health insurance contributions, the previously described confluence indicates a higher probability of infection in groups with socioeconomic disadvantages.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…This can increase risky sexual behaviors such as having multiple sexual partners, engaging in unprotected sexual relations, consuming drugs and alcohol before sex, and using dating apps, among other situations that warrant further study in Medellín. [29][30][31][32][33] The prevalence of HIV was higher in MSM without health insurance affiliation, aligning with a previous study in Colombia that found an infection prevalence of 25% in unaffiliated individuals, 17% for individuals under the subsidized regime, and 9.8% in the contributory regime. Understanding that unaffiliated and subsidized regime individuals correspond to groups without formal employment that involve health insurance contributions, the previously described confluence indicates a higher probability of infection in groups with socioeconomic disadvantages.…”
supporting
confidence: 77%
“…This can increase risky sexual behaviors such as having multiple sexual partners, engaging in unprotected sexual relations, consuming drugs and alcohol before sex, and using dating apps, among other situations that warrant further study in Medellín. 29–33 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, young people express little satisfaction with the sex education provided in schools, which for them is reduced to the prevention of early pregnancy and sexually transmitted diseases, leaving aside other important issues that are part of the integrity of a healthy sexuality (Leiva & Medina, 2022). Therefore, previous analyses emphasize the need to include in sex education programs topics related to sexual identity, expression and orientation, as well as consent to sexual relations at appropriate ages, free from social pressure and violence, taking into account the self-efficacy, reliability, effectiveness and refusal of condom use (Aguirre & Restrepo, 2022; Plaza-Vidal et al, 2021; Sánchez-Mendoza et al, 2020).…”
Section: Discussionmentioning
confidence: 99%